IOT-BASED MONITORING OF AQUACULTURE SYSTEM - Nasir, Omar Abdulhaleem; Mumtazah, Sharifah (MATTER: International Journal of Science and Technology, 2020)
Aquaculture is considered to be a station of interest in many different countries, including Malaysia, which has started on developing its aquaculture system since the 1920s. The two main reasons behind this interest are the great food source for locals and a very good source of income that can help in amazingly increasing the economy of a country, so aquaculture should be well-taken care of, especially, in terms of water quality. Therefore, the main focus and goal of this paper are measuring the water quality parameters that can suit many types of aquacultural living species, especially the fish species. Five sensors are positioned in a one-tone fish tank to measure and monitor the water parameters’ fluctuations, especially during the feeding time. These smart sensors are a waterproof temperature sensor, water PH sensor, water turbidity sensor, air temperature sensor, and light sensor. These sensors are connected to an Arduino board, which sends the collected data from sensors to the GSM and then to Thing speak cloud, which is an easy way to monitor data fluctuations 24 hours a day. As a result, the collected data of water parameters seem to be slightly fluctuating which does not affect the health of the fish in the tank. The reason of choosing these sensors is to also illustrate the statistical correlation between air temperature and water temperature, light intensity and turbidity, turbidity and PH, especially during feeding time. These IoT sensors are very cheap to be bought and easy to be installed and monitored on the cloud. Therefore, this could be very cost-effective for many farmers who want to keep their aquacultural species safe and reproducing.